1992
DOI: 10.1002/ssu.2980080405
|View full text |Cite
|
Sign up to set email alerts
|

Current role of laser and photodynamic therapy in gastrointestinal tumors and analysis of a 10‐year experience

Abstract: Laser energy can be used for a variety of neoplastic diseases including benign tumors, early stage malignancies, and advanced carcinomas, either with curative intent or for palliation. Nd:YAG laser photocoagulation of 168 colorectal adenomas allowed a complete eradication in 70% of cases, after a mean follow-up of 22 months. Advanced and obstructing tumors were treated with Nd:YAG laser to recanalize the lumen. In the upper gastrointestinal tract the recanalization of the lumen by means of laser photocoagulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…High cure rates for benign colon adenomas have been reported with laser therapy in many studies. [16][17][18][19] Endoscopic treatment of asymptomatic non-neoplastic stenosis is one indication for high-power laser therapy. Kiefhaber 18 and Sander and Posel 20 have shown that the high-power laser is effective in opening strictures of E 0 * Significant difference between before and after laser therapy, by Wilcoxson matched-pairs signed-rank test, one-tailed (P Ͻ 0.001) A, The patient is able to eat a solid or normal diet B, The patient is able to take a semiliquid diet smoothly C, The patient is able to drink water or fluid food well D, The patient has difficulty in swallowing a liquid diet and has frequent vomiting E, The patient fails to swallow any food and has vomiting Stenotic lumen impassible by endoscope (lumen Ͻ 9 cm) Before treatment 10 34.5 After treatment 2 6.9…”
Section: Discussionmentioning
confidence: 99%
“…High cure rates for benign colon adenomas have been reported with laser therapy in many studies. [16][17][18][19] Endoscopic treatment of asymptomatic non-neoplastic stenosis is one indication for high-power laser therapy. Kiefhaber 18 and Sander and Posel 20 have shown that the high-power laser is effective in opening strictures of E 0 * Significant difference between before and after laser therapy, by Wilcoxson matched-pairs signed-rank test, one-tailed (P Ͻ 0.001) A, The patient is able to eat a solid or normal diet B, The patient is able to take a semiliquid diet smoothly C, The patient is able to drink water or fluid food well D, The patient has difficulty in swallowing a liquid diet and has frequent vomiting E, The patient fails to swallow any food and has vomiting Stenotic lumen impassible by endoscope (lumen Ͻ 9 cm) Before treatment 10 34.5 After treatment 2 6.9…”
Section: Discussionmentioning
confidence: 99%
“…125 ''Unequivocal visible changes and necrosis'' 125 were noted, the treatment was repeated 6 months later with apparent clinical success, and others have noted similar results. 123,126,127 More recent studies have used colon cell cultures to test new PDT techniques. 128 Del Governatore et al used a photoimmunoconjugate of an anticolon cancer monoclonal antibody with the chlorin photosensitizer NPe6.…”
Section: Pdt For Colorectal Cancermentioning
confidence: 99%
“…PDT has been used to treat superficial esophageal cancer, early lung cancer and early gastric cancer (4)(5)(6). In gynecology, PDT has been used to treat early cancer of the cervix (7).…”
Section: Introductionmentioning
confidence: 99%